Study of passage width considering passing by each other in living space of evacuation centre. (9th August 2019) - Yamato, Yuya; Shen, Zhenjiang; Masrul, Ade Candra
In living room of evacuation centres, there are living spaces and passages. Living space is used for eating and sleep, and passage is common space that many evacuees use every day. Since passages are used for necessary movement in evacuation daily activities, various patterns of passing by each other are considered in passage. In this study, the researchers conducted classification of passage width from the priority level of passing. Then, the passages were organised based on the result of classification. The evacuation centre condition related to the result of classification was also shown. This research contributed to identifying area of passage width needed when making evacuation centre management plan. In addition, this study calculates the capacity from passage width and points out the restricted daily activities. Furthermore, the researchers considered minimum passage width that will be easy for evacuees to pass in evacuation centre.